Comparative Analysis of Rural and Urban Start - Up Entrepreneurs in Nigeria (Global Journal of Human-Social Science, 2014)
The goal of this paper is to understand the different factors of the rate of entrepreneurial intentions in rural and urban settings. Using data from survey we test for factors that are expected to affect entrepreneurial between rural and urban areas. We assume one hypothesis; the main difference of rural and urban entrepreneurs is the different resources in two areas. The resources used in this study are individual resources and contextual resources individual resources are composed of self-efficacy and demographic characteristics, contextual resources consist of social support and economic resources. Using these independent factors, we conducted T-tests to compare different resources in rural and urban areas. The results of the analysis suggest that the difference in available individual, economic and social support resources does not explain the observed difference in entrepreneurship rate. The results also indicate that gender, ethnicity, income, and number of children in the family have different effects on entrepreneurial intentions in rural and urban settings. The results suggest that policy makers need to account for cultural or geographical differences when designing entrepreneurial educational and support programs in order to enhance the establishment of new business between rural and urban areas.
Keywords: start-up entrepreneurs; panel study of entrepreneurial dynamics (PSED)